Penyuluhan Kesehatan Masyarakat Terhadap Peningkatan Kualitas Hidup Masyarakat Di Banyumanik - Widya Ervianta; Lilik Sigit Wibisono; Fitratun Najizah; Anisa Mutiara Hanani; Dana Faricha (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2022)
Health is a valuable asset that we need to take good care of. However, in our daily lives, we often get caught up in hectic routines, poor diets, and unhealthy lifestyles. This is why counseling on improving quality of life is so important. Counseling attempts to raise awareness, provide information, and encourage individuals and communities to adopt healthy behaviors. The counseling materials provided are Preventing Disease and Improving Quality of Life. By increasing awareness of a healthy diet, adequate physical activity, stress management, and other life habits, it can help prevent various chronic diseases such as heart disease, diabetes, and cancer. By adopting healthy behaviors, one can improve their quality of life, reduce the risk of health complications, and enjoy a longer and better life. Increased physical activity or exercise. Physical activity is any movement of the body that causes energy expenditure. The recommendation from the Ministry of Health of the Republic of Indonesia is that physical activity should be done at least 30 minutes per day for 5 times a week or equal to 150 minutes per week. various types of physical activity that can be done such as climbing down stairs, jogging, brisk walking or cycling.